PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGANCORPORATE SOCIAL RESPONSIBILITYSEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Anik Setyowati, 14.05.52.0066; Wahyu Widati,, Listyorini (Students' Journal of Accounting and Banking, 2018)
This study aimed to examinesthe influence of thefirm size, profitability andcorporate social responsibility as a moderating variable on firm value. This research was conducted at Indonesia by using analysis of manufacturing company that have gonepublic.The population of this study is a manufacturing company that listed in the Indonesia Stock Exchange. The sample included in the criteria of this study were 183 companies for 3 years and were selected as research samples of 140 companies with a sampling method using purposive sampling. The technique of data analysis is used moderated with SPSS 21.0 program.The results show that Firm Size (SIZE) and Profitability (ROA) have a significant positive effect on Company Value (PBV), Corporate social responsibility does not moderate the influence of Firm Size (SIZE) and Profitability (ROA) on Company Value (PBV). Keywords:Firm Size, Profitability, Corporate social responsibility and Company Value.